2007
DOI: 10.1051/0004-6361:20078747
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar $^{\mathsf{12}}$C/$^{\mathsf{13}}$C from CH+absorption lines: results from an extended survey

Abstract: Context. The 12 C/ 13 C isotope ratio in the interstellar medium (ISM), and its evolution with time, is an important tracer of stellar yields. Spatial variations of this ratio can be used to study mixing in the ISM. Aims. We want to determine this ratio and its spatial variations in the local ISM from CH + absorption lines in the optical towards early-type stars. The aim is to determine the average value for the local ISM and study possible spatial variations. Methods. We observed a large number of early-type … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…The results for the each LOS are summarized in Table 1 where we have separated the absorption components in the velocity range of the star-forming regions from those originating in unrelated Galactic foreground gas. The 13 CH + and 12 CH + column densities of the foreground gas on the W49N LOS provide a lower limit of the isotopic ratio [ 12 CH + ]/[ 13 CH + ] > 35.5, consistent with the results of Casassus et al (2005); Stahl et al (2008). Three N(CH + )/N(HCO + ) ratios, computed using the observed N(HCO + ) values of Godard et al (2010), are found to be scattered by more than a factor 10.…”
Section: Line Profiles Analysis and Resultssupporting
confidence: 84%
“…The results for the each LOS are summarized in Table 1 where we have separated the absorption components in the velocity range of the star-forming regions from those originating in unrelated Galactic foreground gas. The 13 CH + and 12 CH + column densities of the foreground gas on the W49N LOS provide a lower limit of the isotopic ratio [ 12 CH + ]/[ 13 CH + ] > 35.5, consistent with the results of Casassus et al (2005); Stahl et al (2008). Three N(CH + )/N(HCO + ) ratios, computed using the observed N(HCO + ) values of Godard et al (2010), are found to be scattered by more than a factor 10.…”
Section: Line Profiles Analysis and Resultssupporting
confidence: 84%
“…The 12 C/ 13 C ratio of the solar system (89 ± 1) (Wyckoff et al 2000;Clayton & Nittler 2004) is higher than the interstellar ratio in the solar neighborhood (76 ± 7) (Stahl et al 2008). This difference can be explained by the high 13 C/ 12 C ratio in winds from red giant branch and AGB stars (Timmes et al 1995;Milam et al 2005), although chemical inhomogeneities in the ISM may also be important (Stahl et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be explained by the high 13 C/ 12 C ratio in winds from red giant branch and AGB stars (Timmes et al 1995;Milam et al 2005), although chemical inhomogeneities in the ISM may also be important (Stahl et al 2008). The present-day C and O isotopic composition of the ISM at the Galactocentric location of the Sun's birth is consistent with mixing of average AGB winds with the ISM 4.6 Gyr ago (represented by the solar system) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Gredel 1997;Stahl et al 2008, and references therein). In contrast, being much less affected by interstellar extinction, radio/submm and near infrared absorption observations, e.g.…”
Section: (Sub)millimeter Spectroscopy Of Diffuse Interstellar Cloudsmentioning
confidence: 99%